Bibliometric analysis of research on immunogenic cell death in cancer - Zhou, Yan; Hu, Fen; Cui, Yang; Wu, Haiyang; Hu, Shunan; Wei, Wei (Frontiers in Pharmacology, 2022)
Background: Immunotherapy is changing the way we treat cancer. Immunogenic cell death (ICD) has received considerable attention in the treatments of various cancer types, due to the long-lasting antitumor responses elicited in human body. However, to date, no relevant bibliometric research has been reported. Methods: Publications related to ICD in cancer research were collected from the Web of Science Core Collection. Using CiteSpace, VOSviewer and an online platform, the analyses of co-author, co-citation, and co-occurrence of terms retrieved from literatures were carried out. Results: A total of 1577 publications were included in this study. The global research literatures on ICD in cancer research have been increasing from 2005 to 2021. China, the United States and France dominated in this area and had close collaborations with many countries. Six of the top 10 most contributive institutions were from France. When it comes to author analysis, Kroemer G, Zitvogel L, Kepp O, Garg AD and Galluzzi L were in both the top 10 most productive authors and top 10 most co-cited authors lists. The co-occurring author keywords could be grouped into three clusters: “biomarkers of ICD”, “nanoparticles” and “combination therapy”. In terms of promising hotspots, keywords (author keywords and KeyWords Plus) with recent citation bursts could be summarized into two aspects: “tumor microenvironment” and “nanoparticles”. Conclusions: Increased attention has been paid to ICD in cancer treatment. However, there are still many unresolved domains in the field of ICD, such as clinical application and molecular mechanisms of this cell death process. ICD-inducing modalities combined with nanotechnology could potentiate the current immunotherapies, and will be hotspots for future research.